2013
DOI: 10.1128/aac.01748-13
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Analyses for Efficacy of Ceftaroline Fosamil in Patients with Community-Acquired Bacterial Pneumonia

Abstract: c Pharmacokinetic-pharmacodynamic (PK-PD) analyses for efficacy using phase III trial data from patients treated with a ceftaroline fosamil dosing regimen of 600 mg intravenously (i.v.) every 12 h (q12h) for 5 to 7 days for community-acquired bacterial pneumonia (CABP) were conducted. High clinical and microbiological success rates (84.7 and 86.3%, respectively) and percentages of time during the dosing interval that free-drug steady-state concentrations remained above the MIC (f%T>MIC) (98.4% had f%T>MIC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
10
1
3
Order By: Relevance
“…First, the study here enrolled healthy subjects who typically exhibit decreased pharmacokinetic variability and lower CL T levels compared to infected patients. Previous POP-PK models suggest that subjects in ceftaroline phase 2/3 studies had a 35% higher mean CL T than those in phase 1 studies (27)(28)(29)(30). Given this background, obese class III adults who are acutely infected may theoretically have a higher CL T than that predicted by our model.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…First, the study here enrolled healthy subjects who typically exhibit decreased pharmacokinetic variability and lower CL T levels compared to infected patients. Previous POP-PK models suggest that subjects in ceftaroline phase 2/3 studies had a 35% higher mean CL T than those in phase 1 studies (27)(28)(29)(30). Given this background, obese class III adults who are acutely infected may theoretically have a higher CL T than that predicted by our model.…”
Section: Discussioncontrasting
confidence: 46%
“…This final POP-PK model was relatively similar to a previously published POP-PK model developed with ceftaroline pharmacokinetic data from clinical trials, albeit with some notable differences (27)(28)(29)(30). The previous model utilized three and two compartments for ceftaroline fosamil and ceftaroline, respectively; parallel linear and Michaelis-Menten elimination pathways for ceftaroline; and additional covariates (age, gender, and phase 2/3 patient status).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although PK-PD analyses have been conducted based on clinical data from ceftaroline fosamil-treated patients with ABSSSI and S. aureus at baseline or CABP and S. pneumoniae at baseline (20,21), the results of the analyses described herein were based on nonclinical f %TϾMIC targets for each of these organisms. While PK-PD analyses of patients with ABSSSI and S. aureus isolated at baseline, which were conducted using data from two phase 2 and two phase 3 studies, revealed significant relationships between microbiological response and f %TϾMIC evaluated continuously or categorically, there was a high degree of uncertainty around the identified PK-PD relationships (20).…”
Section: Discussionmentioning
confidence: 99%
“…The cure rates in the ceftaroline arm for S. pneumoniae, penicillin-resistant S. pneumoniae and S. aureus were 85% (54 out of 63), 100% (4 out of 4) and 72% (18 out of 25) while in the ceftriaxone arm the rates were 69% (41 out of 59), 25% (1 out of 4) and 55% (15 out of 27), respectively. According to the PK-PD data obtained from microbiology evaluable population, the majority of patients (91.1%) had ƒ%T > MIC values ranging from 91.7 to 100 [44]. Recently, a similar study using ceftriaxone 2 g every 24 h has also shown the superiority of ceftaroline (84% versus 74%, 95% CI of the difference: 2.8-17) [45 ].…”
Section: Ceftarolinementioning
confidence: 90%